2007
DOI: 10.1007/s00417-007-0633-2
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine-green-mediated photothrombosis (IMP) with intravitreal triamcinolone acetonide for macular edema secondary to group 2A idiopathic parafoveal telangiectasis without choroidal neovascularization: a pilot study

Abstract: Combined IMP and IVTA may provide stability or improvement in BCVA and fundus findings in eyes with macular edema secondary to IPFT group 2A without CNV at a minimum follow-up of 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The results suggested that ICG can be used as a weak photosensitizer for choroidal neovascularisation therapy. Further studies of Navajas et al ( 17 ) and Arevalo et al ( 18 , 19 ) revealed that ICG can be used as a weak photosensitizer in the clinical treatment of cataracts and some other ophthalmic diseases. However, there are relatively fewer studies on ICC treatment of CCH.…”
Section: Discussionmentioning
confidence: 98%
“…The results suggested that ICG can be used as a weak photosensitizer for choroidal neovascularisation therapy. Further studies of Navajas et al ( 17 ) and Arevalo et al ( 18 , 19 ) revealed that ICG can be used as a weak photosensitizer in the clinical treatment of cataracts and some other ophthalmic diseases. However, there are relatively fewer studies on ICC treatment of CCH.…”
Section: Discussionmentioning
confidence: 98%
“…(Chopdar, 1978;Friedman et al, 1993;Gass and Blodi, 1993;Hutton et al, 1978;Kiraly and Nasemann, 1995;Lowe et al, 1998;Park et al, 1997;Stoffelns et al, 2010;Watzke et al, 2005) Obsolete due to side effects (Gass and Blodi, 1993;Lee, 1996;Watzke et al, 2005) Photodynamic ( Alldredge and Garretson, 2003;Cakir et al, 2006;Maguluri et al, 2007;Maia Junior et al, 2006;Martinez, 2003;Wu et al, 2008) --+ Indocyanine green-mediated photothrombosis (Arevalo et al, 2007) Posterior juxtascleral administration of steroids…”
Section: Abbreviationsmentioning
confidence: 99%